(untitled) (Research, Society and Development, 2022)
Psychosocial problems originate from daily wear and tear, either in social life or in the work environment with the possibility of being harmful factors to mental health, in a pandemic scenario, these cases tend to increase in health professionals. In 2020, the World Health Organization declared COVID-19 a pandemic. Thus, health professionals suffer an immense psychological pressure, and with this there is an increase in the rates of disease s, because the work environment at the hospital level requires high rational and physical commitment. The aim of this study was to identify psychosocial problems in the multidisciplinary team working at the Tucuruí-Pa Municipal Hospital in a pandemic scenario. It’s a descriptive research with quantitative approach, had as target population 37 health professionals, and the instrument of data collection was an online questionnaire adapted on the Google Forms platform®, the Depression Anxiety Anxiety Scale (DASS-21, demonstrating a percentage of 64.86% with extreme anxiety and 10.81% with severe anxiety, for cases of depression it was possible to identify 54.05% with depression presenting in the extreme form, and in the severe form 8.11%, for cases of stress 48.65% with extreme stress and 10.81% with severe stress, demonstrating a high rate of anxiety, depression and stress in these professionals, being urgent a new look at the RAPS (Psychosocial Care Network) that welcome this population that is a user of the SUS.